SCHOOL-BASED MENTAL HEALTH: PARADIGM SHIFT IN ADDRESSING MENTAL HEALTH OF PAKISTANI YOUTH - Waqar, Mahnoor; Naveed, Sadiq (Journal of Pakistan Psychiatric Society, 2024)
About 20-25% of the youth suffer from mental and substance use disorders. About 50% of these mental disorders have an onset before age 15, and 75% by 25 years contributing to about five trillion dollars of economic losses every year. Youth’s mental health is imperative in how they think, behave, and learn. School is a critical place in the lives of developing youth, presenting a unique place for prevention and early interventions. Developed countries, such as the United States of America (USA), Canada, the United Kingdom, and Australia, have established a framework that focuses on enhancing teachers’ efficacy in recognizing warning signs for mental health problems. They also liaise with school counselors and mental health professionals to ensure that at-risk individuals get appropriate help for early prevention. Moreover, students are also taught about mental health problems to raise awareness and reduce the stigma associated with it. Pakistan is also making considerable progress to counter mental health in its youth. The School Mental Health Programmes for teachers and Theory of Change model are a few examples of initiatives taken by our government in collaboration with other stakeholders which have shown promise in addressing the mental health problems in children. Moving forward it is essential for the stakeholders, policymakers, and state institutions to collaboratively build a framework that serves the mental health needs of the Pakistani youth, keeping in perspective the cultural context and limited infrastructure.